2008
DOI: 10.1002/jsfa.3120
|View full text |Cite
|
Sign up to set email alerts
|

Mineral contents of some aromatic plants, their growth soils and infusions

Abstract: BACKGROUND: In this study, 18 kinds of medicinal plants were collected together with their soils from different regions of Turkey and their macro-and micro-element and heavy metal contents were determined by inductively coupled plasma atomic emission spectrometry (ICP-AES). In soils, pH, electrical conductivity, carbonate (lime), organic matter, texture, P, K, Ca, Mg, Fe, Cu, Mn, Zn and B were analysed. In plants and extracts, P, K, Ca, Mg, Fe, Cu, Mn, Zn, B, Na, Al, Li, Pb, Ni, Cd, Co and Cr contents were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
41
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 12 publications
6
41
1
2
Order By: Relevance
“…The chromium level in the analyzed plants (under 1 mg/kg, except mint, plantain, and lavender) in other papers is either approximately the same for lavender [42, 57] and for mint [43, 46] or greater for coriander, chamomile, and dill [42, 43, 45, 58]. These papers state Cr recoveries, depending on the preparation method used, in the infusions of 3.6 to 10.9% (coriander, mint, and chamomile, 2.5 g plant in 50 ml water, [46]) or 59 to 80% (chamomile, 2 g dry plant in 100 ml boiling or hot water, 5 minutes, [58]).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The chromium level in the analyzed plants (under 1 mg/kg, except mint, plantain, and lavender) in other papers is either approximately the same for lavender [42, 57] and for mint [43, 46] or greater for coriander, chamomile, and dill [42, 43, 45, 58]. These papers state Cr recoveries, depending on the preparation method used, in the infusions of 3.6 to 10.9% (coriander, mint, and chamomile, 2.5 g plant in 50 ml water, [46]) or 59 to 80% (chamomile, 2 g dry plant in 100 ml boiling or hot water, 5 minutes, [58]).…”
Section: Discussionmentioning
confidence: 86%
“…These papers state Cr recoveries, depending on the preparation method used, in the infusions of 3.6 to 10.9% (coriander, mint, and chamomile, 2.5 g plant in 50 ml water, [46]) or 59 to 80% (chamomile, 2 g dry plant in 100 ml boiling or hot water, 5 minutes, [58]). From the data of [59], the calculated chromium transfer in boiling water (1 g of plant powder in 200 ml water) for mint is 23.5% and for chamomile 17.6%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous scientific studies, all over the world on nutritive composition of wild plants high quantities of minerals, especially K, Na, Ca, P, Mg (Guil Guerrero et al, 1998;Agrahar-Murugkar and Subbulakshmi, 2005) are indicated. Iron values were reported between 10 and 981 mg kg -1 with highest value determined in sage (Zengin et al, 2008). Se values were reported between 0.0015 and 0.4 mg kg -1 with the highest value determined in Solenostemma arghel (Sheded, 2006).…”
Section: Discussionmentioning
confidence: 91%